2003
DOI: 10.1007/s00216-003-1770-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of quaternary mixtures by the apparent content curves method: identification of tocopherols in vegetable oils

Abstract: A procedure for identification of the compounds in quaternary mixtures has been developed. The proposed procedure is based on the apparent content curves method. From these curves and using the Q parameter, work conditions are selected and quaternary mixtures treated as "pseudoternary" mixtures.A simple strategy to test matrix effects at working wavelengths has been developed, identification limits established and following the identification table quaternary mixtures were easily characterised. The procedure h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Różnice w widmach fluorescencyjnych poszczególnych olejów, uzyskane w danych warunkach pomiaru, wynikają ze zróżnicowania ilościowo-jakościowego składu związków wykazujących naturalną emisję, takich jak: tokoferole, chlorofile oraz związki fenolowe [5,9,16,17].…”
Section: Wyniki Dyskusjaunclassified
“…Różnice w widmach fluorescencyjnych poszczególnych olejów, uzyskane w danych warunkach pomiaru, wynikają ze zróżnicowania ilościowo-jakościowego składu związków wykazujących naturalną emisję, takich jak: tokoferole, chlorofile oraz związki fenolowe [5,9,16,17].…”
Section: Wyniki Dyskusjaunclassified
“…The quaternary mixture of tocopherols in edible oils has been characterized by fluorimetry by using the apparent content curves method (ACC). 32 The ACC method is applied to the synchronous spectra of tocopherols in hexane and in isopropanol. It was observed that the excitation spectra are different for the different tocopherols, while the emission spectra have the same shape.…”
Section: Introductionmentioning
confidence: 99%